A T‐cell reporter platform for high‐throughput and reliable investigation of TCR function and biology. Issue 11 (23rd November 2020) - Müller, Thomas R; Schuler, Corinna; Hammel, Monika; Köhler, Amelie; Jutz, Sabrina; Leitner, Judith; Schober, Kilian; Busch, Dirk H; Steinberger, Peter
Abstract: Objective: Transgenic re‐expression enables unbiased investigation of T‐cell receptor (TCR)‐intrinsic characteristics detached from its original cellular context. Recent advancements in TCR repertoire sequencing and development of protocols for direct cloning of full TCRαβ constructs now facilitate large‐scale transgenic TCR re‐expression. Together, this offers unprecedented opportunities for the screening of TCRs for basic research as well as clinical use. However, the functional characterisation of re‐expressed TCRs is still a complicated and laborious matter. Here, we propose a Jurkat‐based triple parameter TCR signalling reporter endogenous TCR knockout cellular platform (TPR KO ) that offers an unbiased, easy read‐out of TCR functionality and facilitates high‐throughput screening approaches. Methods: As a proof‐of‐concept, we transgenically re‐expressed 59 human cytomegalovirus‐specific TCRs and systematically investigated and compared TCR function in TPR KO cells versus primary human T cells. Results: We demonstrate that the TPR KO cell line facilitates antigen‐HLA specificity screening via sensitive peptide‐MHC‐multimer staining, which was highly comparable to primary T cells. Also, TCR functional avidity in TPR KO cells was strongly correlating to primary T cells, especially in the absence of CD8αβ co‐receptor. Conclusion: Overall, our data show that the TPR KO cell lines can serve as a surrogate of primary human T cells for standardised and high‐throughput investigation of TCR biology. Abstract : A highly sensitive triple parameter T‐cell receptor (TCR) reporter cell line was adapted for high‐throughput testing of transgenically expressed TCRs by CRISPR/Cas9‐mediated deletion of the endogenous TCR and introduction of the CD8αβ co‐receptor. Using 59 CMV‐specific TCRs, we demonstrated a high similarity with primary T cells in terms of multimer staining, functional avidity and CD8‐dependence. In conclusion, we present a T‐cell reporter platform excellently suited for high‐throughput functional preclinical testing of TCRs.